Evidence of Reduced Efferent Renal Sympathetic Innervation After Chemical Renal Denervation in Humans. (2nd March 2021) - Hearon, Christopher M; Howden, Erin J; Fu, Qi; Yoo, Jeung-Ki; Dias, Katrin A; Roberts-Reeves, Monique A; Samels, Mitchel; Sarma, Satyam; Nesbitt, Shawna; Vongpatanasin, Wanpen; Goldstein, David S; Addo, Tayo; et al.
Abstract: BACKGROUND: Renal denervation (RDN) is effective at lowering blood pressure. However, it is unknown if ablative procedures elicit sympathetic denervation of the kidneys in humans. The aim of this investigation was to assess sympathetic innervation of the renal cortex following perivascular chemical RDN, which may be particularly effective at ablating perivascular efferent and afferent nerves. METHODS: Seven hypertensive patients (4F:3M; 50–65 years) completed PET–CT sympathetic neuroimaging of the renal cortex using 11 C-methylreboxetine ( 11 C-MRB, norepinephrine transporter ligand) and 6-[ 18 F]-fluorodopamine ( 18 F-FDA; substrate for the cell membrane norepinephrine transporter) before and 8 weeks after chemical RDN (Peregrine System Infusion Catheter, Ablative Solutions; n = 4; 2F:2M) or control renal angiography ( n = 3; 2F:1M). Patients completed physiological phenotyping including 24-hour ambulatory blood pressure, hemodynamics, muscle sympathetic nerve activity, and 24-hour urine collection. RESULTS: RDN decreased 11 C-MRB-derived radioactivity by 30% (Δ 11 C-MRB/chamber: −0.95 a.u. confidence interval (CI): −1.36 to −0.54, P = 0.0002), indicative of efferent RDN. In contrast, 18 F-FDA-derived radioactivity increased (Δ 18 F-FDA/chamber: 2.72 a.u. CI: 0.73–4.71, P = 0.009), consistent with reduced vesicular turnover. Controls showed no change in either marker. Ambulatory systolic pressure decreased in 3 of 4 patients (−9 mm Hg CI: −27 to 9, P = 0.058), and central systolic pressure decreased in all patients (−23 mm Hg CI: −51 to 5, P = 0.095). CONCLUSIONS: These results are the first to show efferent sympathetic denervation of the renal cortex following RDN in humans. Further studies of mechanisms underlying variable blood pressure lowering in the setting of documented RDN may provide insights into inconsistencies in clinical trial outcomes. CLINICAL TRIALS REGISTRATION: Trial Number NCT03465917.